INVESTIGATION OF HEAVY METAL CONTENTS IN THE SEDIMENT AND WASTE WATER, WATER ALONG THE ARAB-KAND CHANNEL (ERBIL, NORTH OF IRAQ) - RASOOL, REZHNA ALİ (Fırat Üniveristesi, 2023)
Erbil şehri atıksuyu, Arap-Kand kanalı boyunca Turak kasabasından Zap suyuna yaklaşık 40 km boyunca akmaktadır. Bu çalışma yaklaşık 40 km. uzunluğundaki kanal güzergahı boyunca kanal içindeki su ve sedimentlerdeki ağır metal kirliliğinin boyutlarının incelenmesini amaçlanmıştır. Bu amaç için Erbil'den güneye doğru farklı mesafelerde kanal güzergâhı boyunca 5 farklı noktadan sediment örneği, 3 ayrı noktadan ise su örnekleri alınmıştır. Bu su ve sediment örnekleri Acme (Kanada) analiz laboratuvarında yaklaşık 70 element için analizleri yapılmıştır. Aynı zamanda kirlenmiş su örneklerinin anyon ve katyon analizleri ile fizikokimyasal parametreleri de ölçülmüştür. Bu çalışmaların sonucunda, yöredeki Arap-Kand kanalı boyunca hem atık sular, hem de sedimentler yoğun olarak ağır metallerce kirlenmiştir. Özellikle, Sr, Zn, Pb, Cd ve Ni gibi metaller, hem suda, hem de sedimentlerde önemli oranda zenginleşmiştir. Bu atık sular biyolojik açıdan da önemli oranda kirlenmiş olmasına rağmen, yöredeki çiftlikler hem hayvanların sulanması, hem de tarımsal sulama da kullanıyor olması, gelecekte hem çevre hem de gıda zinciri için önemli halk sağlık problemlerine yol açacaktır. Bu suların kesinlikle sulama ve içme amaçlı kesinlikle kullanılmamalıdır.

Erbil city wastewater flows along the Arap-Kand channel from Turak town to Zap water for about 40 km. This work is approximately 40 km. In this study, it is aimed to examine the dimensions of heavy metal pollution in the water and sediments in the canal along the length of the canal route. For this purpose, sediment samples were taken from 5 different points and water samples from 3 different points along the canal route at different distances from Erbil to the south. These water and sediment samples were analyzed for approximately 70 elements in the Acme (Canada) analysis laboratory. At the same time, anion and cation analyzes and physicochemical parameters of the contaminated water samples were also measured. As a result of these studies, both wastewater and sediments along the Arap-Kand canal in the region were heavily polluted by heavy metals. In particular, metals such as Sr, Zn, Pb, Cd and Ni were significantly enriched in both water and sediments. Although these wastewaters are also highly polluted from a biological point of view, the fact that the farms in the region use both animal watering and agricultural irrigation will cause important public health problems for both the environment and the food chain in the future. These waters should never be used for irrigation and drinking purposes.
Arab-Kand Kanalı (Erbil, Kuzey Irak) boyunca sediment ve atık sudak ağır metal içeriklerinin araştırılması
Keywords: Jeoloji Mühendisliği